Two-phase mixture model for substrate degradation and photo-hydrogen production in an entrapped-cell photobioreactor under various light intensities. Issue 22 (11th March 2015) - Guo, Cheng-Long; Cao, Hong-Xia; Pei, Hong-Shan; Guo, Fei-Qiang; Liu, Da-Meng
<x xml:space="preserve">Abstract</x> Substrate degradation and photo-hydrogen production under various light intensities was predicted using the developed two-phase mixture model.